Hypolipidemic Effect of Chloroform Extract of Lagenaria siceraria: Potential Inhibitory Activity of Phytochemicals Targeting the HMG-CoA Reductase Revealed by Molecular Docking and Simulation Studies - Qudsia Kanwal; Mahmood Ahmed; Atiq Ur-Rehman; Aneela Anwar; Samiah Shahid; Atif Shahzad; Attaullah Shah Bukhari; Muhammad Ahmad; Numan Yousaf; Muhammad Muddassar (Journal of Chemistry, 2023)
Conventional systems of medicine play a crucial role in maintaining healthcare. Herbal medicines are intact and less harmful to human beings than synthetic medicines. This study aimed to investigate the phytochemicals and in vivo hypolipidemic effect of chloroform extract of Lagenaria siceraria in Triton X-100 (100 mg/kg body weight) induced hyperlipidemic Wistar rats. The phytochemical characterization and estimation were performed on the base of the GC-MS approach. The Lagenaria siceraria extract (250 and 500 mg/kg bw) was administered orally to hyperlipidemic-induced rats for 7 days to examine its hypolipidemic activity. The experimental animals did not display any acute toxicity. Atorvastatin (10 mg/kg bw) was used as a standard drug. Administration of Lagenaria siceraria extract lowers the total cholesterol (TC), triglyceride (TG), and low-density lipoproteins-cholesterol (LDL-C) levels whereas elevating the high-density lipoproteins-cholesterol (HDL-C) level. Histological studies of the liver and heart also showed the hypolipidemic effect of the extract. On the 8th day, no inflammation of the liver, myocardial necrosis, fibrosis, or atypia was seen. Furthermore, binding affinity and plausible binding mode of stigmastan-3-ol with HMG-CoA reductase were predicted by molecular docking studies which showed the same interaction patterns as atorvastatin. Moreover, the docking results were refined by 100 ns MD simulations which revealed that stigmastan-3-ol extract formed a stable complex with protein and did not induce any conformational changes in protein structure.